2021
DOI: 10.2166/wpt.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Chromium and nickel metal ions removal from contaminated water using Nigerian bentonite clay

Abstract: In this work bentonite clay was characterized and investigated for the adsorption of chromium and nickel metal ions from aqueous solution. The clay calcined at 650 °C was characterized for physical, chemical and textural properties. Nickel sulphate hexahydrate (NiSO4.6H2O) and chromium tri oxide (Cr2O3) solutions were used as metal model compounds to evaluate the adsorption efficiency of the clay in a batch mode. The initial metal ions concentration range from 10 to 50 mg/L and the maximum removal efficiency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…At 600 ppm, the removal efficiency of Cr (VI) decreases as insufficient availability of active sites, thus causing the saturation of the adsorbent's surface at equilibrium. Similar initial Cr (VI) concentration effects on removal trends were observed for absorbents prepared from iron-based solid waste and bentonite clay by Qi et al (2023) and Jock et al (2021), respectively.…”
Section: Effect Of Initial Concentrationsupporting
confidence: 67%
See 1 more Smart Citation
“…At 600 ppm, the removal efficiency of Cr (VI) decreases as insufficient availability of active sites, thus causing the saturation of the adsorbent's surface at equilibrium. Similar initial Cr (VI) concentration effects on removal trends were observed for absorbents prepared from iron-based solid waste and bentonite clay by Qi et al (2023) and Jock et al (2021), respectively.…”
Section: Effect Of Initial Concentrationsupporting
confidence: 67%
“…Cr (VI) ions removal was drastically increased by 35.0% with the increase in initial concentration from 100 ppm to 300 ppm. This observation might be caused by the adsorbent surface having a large number of active sites available, which would increase the Cr (VI) adsorption (Jock et al, 2021). The percentage removal continued to increase by 6.4% at 400 ppm and thereafter achieved the highest removal of 88.4% at 500 ppm.…”
Section: Effect Of Initial Concentrationmentioning
confidence: 99%
“…These results confirm that neither Cr(III) nor Cr(VI) significantly changed the valency state after adsorption with NTB and MTBs. A previous study reported that the forms of Cr(III) at pH 4.2–12 were Cr 2 O 3 and minor Cr(OH) 3 [58]. These cation forms in the bulk solution were exchangeable with polycations of the bentonite surface, including Ca 2+ , Mg 2+ , Na + , and K + cations [59].…”
Section: Resultsmentioning
confidence: 99%